Comparison of the efficacy and safety of 3 months of CAPOX followed by 3 months of capecitabine and 6 months of CAPOX/FOLFOX in the adjuvant treatment of low-risk stage-III colon cancer treated surgically - Bardakci, Murat; Esmer, Derya; Hafizoglu, Emre; Yaslikaya, Sendag; Genc, Tugrul Burak; Ozcelik, Melike; Sendur, Mehmet Ali Nahit (Karger, 2023)
Introduction: In the adjuvant treatment of low-risk stage-III colon cancer treated surgically, 3 months of CAPOX followed by 3 months of capecitabine is not a common clinical practice. Since there are no data on this practice in the literature, we have no idea how often it is used. However, it should be noted that this application is used in some centers due to the cumulative neurotoxicity of oxaliplatin but there are insufficient data in the literature on its efficacy.Methods: The data of patients with colon cancer treated surgically who were followed up in 12 different oncology centers in Turkey between November 2004 and June 2022 were analyzed retrospectively.Results: The study included 194 patients. The treatment arms were as follows: 3 months of CAPOX followed by 3 months of capecitabine = arm A and CAPOX/FOLFOX (6 months) = arm B. There were 78 patients (40.2%) in arm A and 116 patients (59.8%) in arm B. The median age and sex distribution were similar between the treatment arms. The median follow-up period of all patients was 34.4 months (95% CI, 29.1-39.7). When arm A was compared with arm B, 3-year disease-free survival (DFS) was 75.3% vs. 88.4% and 5-year DFS was 75.3% vs. 82.8%, respectively. There were similar DFS outcomes between the treatment arms (p=0.09). Rates of any grade of neuropathy were numerically lower in arm A, but the difference between the treatment arms was not statistically significant (51.3% vs. 56.9%; p=0.44). The frequency of neutropenia was similar between the treatment arms.Discussion/Conclusion: In this study, the efficacy and safety of the 3 months of CAPOX followed by 3 months of capecitabine chemotherapy regimen in the adjuvant treatment of low-risk stage-III colon cancer treated surgically was proven. This result may also support the discontinuation of oxaliplatin at 3 months while continuing fluoropyrimidines, which is a common clinical practice but lacks sufficient data.
Keywords: Fluorouracil; Oxaliplatin; Leucovorin; Chemotherapy; Survival; Idea